PERANAN SATUAN POLISI PAMONG PRAJA MENJALANKAN PERATURAN KEPALA DAERAH (PERDA) MENUJU PROGRAM PERCEPATAN PEMBANGUNAN DAERAH KABUPATEN BURU SELATAN - LILIGOLI, ALFRET (Patria Artha University, 2021)
This study aims to determine the role of the Civil Service Police Unit in implementing regional regulations, especially those related to the Regional Development Acceleration Program, and to find out what factors are the obstacles for the Civil Service Police Unit in carrying out regional regulations in South Buru Regency.This research is descriptive using a qualitative approach so that to support this research activity, data collection from informants was carried out. Data analysis is preceded bycollecting and collecting data or information in the field, after which it is classified according to the type and group, then it is then analyzed or interpreted qualitatively. Based on the results of the analysis, it is known that in order to support the South Buru Regency Regional Development Acceleration Program, to realize the enforcement of the South Buru Regency regional regulations, the Civil Service Police Unit has a reference, namely based on statutory regulations. but still not optimal. This is due to the quality aspect of local government officials, as well as the existence of various obstacles regarding the mechanism for imposing sanctions. Factors that become obstacles for the Civil Service Police Unit in implementing the regional regulations of South Buru Regency. influencing the enforcement of regional regulations in South Buru Regency by the Civil Service Police Unit within the scope of the South Buru Regency Government, namely, among others, the quality of human resources and facilities and infrastructure both in the form of official vehicles and operational funding assistance, enforcement of penal sanctions and a large working area.